Financial Technology: Inclusive Finance in the Post-Covid-19 Era - Susanto, Bambang; Ratnawati, Aryanti; Rachmawati, Eva; Setiawan, Audita; Khalingga, Muhammad Ariq (ADPEBI International Journal of Business and Social Science, 2022)
Purpose – This paper aims to investigate how the optimization or effectiveness of the use of financial technology in the volume of stock trading with the JCI as an indicator in the Indonesian capital market that occurred before the Covid-19 pandemic and after or during the Covid-19 pandemic remained active and did not affect investor behavior in invest Methodology – The research method used in this research is descriptive analysis technique, and the data used is normally distributed. The data collection technique uses a quantitative approach , including stock transaction volume data with the JCI indicator at PT. Indonesia Stock Exchange before and after the covid 19 virus pandemic. Findings – From the analysis it was found that the volume of stock trading in PT. The Indonesia Stock Exchange during the COVID-19 pandemic was larger than before the COVID-19 pandemic. From the calculation of the NGain Score, the use of financial technology was more effective and optimal for use in the post-pandemic period than in the pre-pandemic period. Value – Empirical studies conducted usually look at how much influence the COVID-19 pandemic has on the level of the economy, but this research looks at how investor behavior is in optimizing or effectively using financial technology in the period before and after the COVID-19 pandemic.